Opium use and the risk of head and neck squamous cell carcinoma. Issue 5 (9th October 2020) - Mohebbi, Elham; Hadji, Maryam; Rashidian, Hamideh; Rezaianzadeh, Abass; Marzban, Maryam; Haghdoost, Ali Akbar; Naghibzadeh Tahami, Ahmad; Moradi, Abdolvahab; Gholipour, Mahin; Najafi, Farid; Safari‐Faramani, Roya; Alizadeh‐Navaei, Reza; et al.
Abstract: Scant evidence exists to support the association of opium use with head and neck cancer, limited to the larynx and oral cavity. In a multicenter case‐control study—Iran Opium and Cancer study, we recruited 633 cases of head and neck squamous cell carcinoma (HNSCC) (254 lip and oral cavity, 54 pharynx, 327 larynx and 28 other subsites within the head and neck) and 3065 frequency‐matched controls from April 2016 to April 2019. Odds ratios (ORs) for opium use and 95% confidence intervals (95% CIs) were obtained using mixed‐effects logistic regression because of heterogeneity among centers. The adjusted OR (95% CI) for regular opium use was 3.76 (2.96‐4.79) for all HNSCC combined. Strong dose‐response effects were observed by frequency or amount of use, and duration of use. Regular opium uses significantly increased the risk of HNSCC of the pharynx, larynx and other subsites within the head and neck with OR (95% CI) of 2.90 (1.40‐6.02), 6.55 (4.69‐9.13) and 5.95 (2.41‐14.71), respectively. The observed associations were significant even among never tobacco smokers (including cigarette and water‐pipe smoking). Moreover, by the multiplicative interaction scale, the effect of opium use could be varied by cigarette smoking on HNSCC, 8.16 (6.20‐10.74). For the first time, the current study showed opium users have an increased risk of several anatomic subsites of HNSCC. Abstract : What's new? Opium use has been associated with the risks of several cancers, but there is little data on whether opium contributes to head and neck cancer risk. Here, the authors conducted a multicenter case‐control study, the Iran Opium and Cancer study (IROPICAN). They recruited 633 cases of head and neck squamous cell carcinoma and 3065 controls. The study drew from 10 provinces in Iran where opium use is most prevalent. They found that regular opium users have an elevated overall risk of HNSCC, and laryngeal cancer in particular.